2014
DOI: 10.3126/njms.v3i1.10354
|View full text |Cite
|
Sign up to set email alerts
|

Factors affecting Early Age Marriage in Dhankuta Municipality, Nepal

Abstract: Background:Child marriage defined by UNICEF as marriage before 18 years of age is a reality for more than 60 million women worldwide.1 The practice has become increasingly recognised as a human rights violation 2,3 and has decreased worldwide during the past 20 years.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
16
0
1

Year Published

2016
2016
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(19 citation statements)
references
References 8 publications
2
16
0
1
Order By: Relevance
“…In a study conducted by Sah et al in Nepal, ethnicity was also observed to be a major factor influencing early marriage (p<0.001). [21] Factors such as religion, form of education, age of respondents at first marriage and type of family were not found to significantly influence the practice of early marriage in this study (p>0.05).…”
Section: Section: Community Medicinementioning
confidence: 80%
“…In a study conducted by Sah et al in Nepal, ethnicity was also observed to be a major factor influencing early marriage (p<0.001). [21] Factors such as religion, form of education, age of respondents at first marriage and type of family were not found to significantly influence the practice of early marriage in this study (p>0.05).…”
Section: Section: Community Medicinementioning
confidence: 80%
“…Similar observations were made by a study conducted by Sah RB et al (82.9%). 7 The association of poverty and early marriage has been emphasized by Jennifer Birech where it is quoted that in the presence of acute poverty, a young girl may be seen as an economic burden, when purchased will relieve the family financially and socially. 1 Hence, marriage is considered a transaction, a significant economic activity for the family without considering its impact on the young woman.…”
Section: Discussionmentioning
confidence: 99%
“…This was comparable to a study conducted by Sah RB et al wherein 65% of women who got married before the age of 18 years were educated below SSLC. 7 A study carried out in Bangladesh has shown that one year of delay in marital age would have increased female years of schooling by 3 years and probably lead to 6.5% higher female literacy. 8 It was observed in our study that 81% of mothers who lived below poverty line 9 got married before the age of 18 years.…”
Section: Discussionmentioning
confidence: 99%
“…Parsons et al (2015) states that girls whose mothers have lower education levels are more likely to experience child marriage. Studies abroad also indicate that educational level is one facto causing child marriages (Stang & Mambaya, 2011;Sah, Subedi, Shah, & Jha, 2014). Low educational level will potentially make children marry at an early age, because they do not have sufficient knowledge about the consequences of child marriages.…”
Section: Discussionmentioning
confidence: 99%
“…On the other hand, the solution to overcome financial needs is that they must marry. Other studies also revealed that parents tend to marry off their children to household and independent burdens (Stang & Mambaya, 2011;Astuty, 2013;Sah et al, 2014). Judging from the data in the field, some couples still experience difficult economic conditions, and their parents still have to bear daily costs of the married child and her husband.…”
Section: Discussionmentioning
confidence: 99%